2021
DOI: 10.21037/atm-21-934
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid prompts bone formation in ovariectomized osteoporotic rats and weakens osteoclast formation after treatment with ultraviolet B

Abstract: Background: Ultraviolet B (UVB) has been reported to prevent bone loss by promoting the synthesis of vitamin D. However, UVB can also enhance osteoclastic differentiation, inhibit osteogenic differentiation, and cause oxidative damage. The present study aimed to analyze the osteoprotective effects of UVB and conjugated linoleic acid (CLA) in rats with ovariectomy-induced osteoporosis, and to determine the interactions between UVB and CLA and their effects on bone mesenchymal stem cells (BMSCs) and bone marrow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It was interesting to note that ICA administration also significantly up-regulated the precursor of stearidonic acid, i.e., linoleic acid, by FC of 1.36 ( p < 0.05), which was 1.32 times of E2 group ( p < 0.05). The relationships between linoleic acid and bone biology have been widely studied and recently verified to promote bone formation in OVX rats by co-working with ultraviolet B treatment ( 55 , 56 ). L-Saccharopine is an important metabolite in amino acid metabolism and often decrease during the progression of OP and PMOP ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was interesting to note that ICA administration also significantly up-regulated the precursor of stearidonic acid, i.e., linoleic acid, by FC of 1.36 ( p < 0.05), which was 1.32 times of E2 group ( p < 0.05). The relationships between linoleic acid and bone biology have been widely studied and recently verified to promote bone formation in OVX rats by co-working with ultraviolet B treatment ( 55 , 56 ). L-Saccharopine is an important metabolite in amino acid metabolism and often decrease during the progression of OP and PMOP ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that BSZJD has potential anti-osteoporotic effects through mass spectrometry analysis-network pharmacology-molecular docking. The active ingredients of BSZJD possess similar pharmacological effects, including immunomodulatory, anti-in ammatory and antioxidant effects [10,11] . Triterpenoids (e.g., porinic acid) can regulate the RANKL-medi.ated NF-κb and Nfatc1 signaling pathway, inhibit RANKL and RANKJ binding, and thus inhibit osteoclast proliferation and differentiation [12] .…”
Section: Discussionmentioning
confidence: 99%
“…The production of mineralized nodules of osteoblasts was observed (Rahman et al., 2014). Continuous administration of different concentrations of CLA (1.4/2.8/4.2 mmol/kg) for 24 weeks stimulated new bone formation and inhibited TRAP activity in a dose‐dependent manner (Shan et al., 2021). In a Mendelian randomization study of 53,236 patients with osteoporosis, it was established that consumption of dairy products rich in omega‐3 fatty acids reduced serum PTH and RANKL (Wang, Zhang, et al., 2022).…”
Section: Role Of Milk Components On Osteoporosis Modulationmentioning
confidence: 99%